The Involvement of Sortilin/NTSR3 in Depression as the Progenitor of Spadin and Its Role in the Membrane Expression of TREK-1 - Jean Mazella (Frontiers in Pharmacology, 2019)
The molecular identification of sortilin, also called neurotensin receptor-3, from three different biochemical approaches already predicted the involvement of the protein in numerous biological and cellular functions. The first important observation was that sortilin is synthesized as a precursor that is converted to a mature protein after cleavage by the protein convertase furin in late Golgi compartments. This maturation leads to the formation of a 44 amino acid peptide, the propeptide (PE). The release of this peptide when matured sortilin reached the plasma membrane remained to be demonstrated. Sortilin has been also shown to be shedded by matrix metalloproteases releasing a large extracellular fragment identified as soluble sortilin. Therefore, sortilin has been shown to interact with several proteins and receptors confirming its role in the sorting of cellular components to the plasma membrane and/or to the lysosomal pathway. Interestingly, sortilin physically interacts with the two pore domain potassium channel TREK-1 and the PE as well as its synthetic analog spadin is able to block the activation of TREK-1 highlighting their role in the depression pathology. The present review describes the advance of research that led to these results and how both the soluble form of sortilin and the sortilin-derived PE have been detected in human serum and whose levels are affected in patients with major depressive disorder (MDD). The use of spadin as an antidepressant and the further role of soluble sortilin and of sortilin-derived PE as potential biomarkers during depression statement and/or remission of the pathology are considered and discussed in this review.